Методичні підходи до оцінки часу на реалізацію інноваційних проектів в сфері інформаційних технологій - Перерва, Петро Григорович; Назаренко, Станіслав Миколайович (НТУ "ХПІ", 2018)
В статті виявлено проблеми, які зустрічаються при оцінці часу на реалізацію інноваційних проектів. Досліджено основні методи оцінки витрат часу на реалізацію інноваційних проектів. Визначено переваги та недоліки, а також обґрунтовано пропозиції щодо використання кожної з методик (технік). Доведено доцільність комбінації технік для досягнення найбільш точного результату оцінки часу. Це дозволить мінімізувати ризики, пов'язані з невчасним виконанням проектів, що несе за собою штрафні санкції та втрату репутації компанії, що є неприйнятним в умовах жорсткої конкуренції та не сприяє подальшому розвитку сектору інформаційних технологій.

The article reveals the problems encountered in evaluating the time for the implementation of innovative projects. The main methods of estimating the time expenditures for the implementation of innovative projects are investigated. The advantages and disadvantages are determined, as well as suggestions on the use of each method (technique) are substantiated. The expediency of a combination of techniques to achieve the most accurate result of time estimation has been proved. This will minimize the risks associated with late implementation of projects, which entails penal sanctions and loss of company reputation, which is unacceptable in the face of fierce competition and does not contribute to the further development of the information technology sector.
Methodical approaches to evaluation of the time for implementation of innovative projects in the field of information technologies
Keywords: естимація; оцінка часу; інноваційні проекти; інформаційні технології; аутсорсинг; estimation; estimation of time; innovative projects; information technologies; outsourcing